Pemberdayaan Perempuan dalam Pembangunan Ekonomi Syariah di Desa Kedungdowo, Kecamatan Andong, Kabupaten Boyolali - Yuni Safitri; Izzun Khoirun Nisa (LPMP Imperium, 2025)
This community service program focuses on empowering women in the development of the Sharia economy in Kedungdowo Village, Andong District, Boyolali Regency. The program is implemented in February 2025 with the aim of enhancing women's understanding and skills in managing Sharia-based finances and developing micro-businesses in accordance with Islamic economic principles. Through a participatory approach and practical training, participants receive materials and intensive mentoring to apply Sharia financial concepts in their daily lives. The success of this program is measured by the improvement in participants' understanding of the Sharia economy, their financial management skills, and the growth of their micro-businesses after attending the training. Evaluations show that 50 participants experienced significant progress in these aspects, as reflected in better financial management practices and the sustainability of their businesses. With these positive results, this program is expected to serve as a sustainable model for women's empowerment based on the Sharia economy in other regions.